Delivery of Counselling and Psychological Services in a Faculty of Education - Thompson, A. P.; Young, R. A.; Keffer, A.; Wigmore, R. (Canadian Journal of Counselling and Psychotherapy, 2012)
Professional faculties within the university community are ideal settings for preventative, outreach counselling. Efforts by a university counselling center to provide psychological services to a faculty of education are described. This account deals with issues such as role definition, in-service training, publicity and mode of delivery (individual, group, psychological education). The difficulties of programme evaluation and psychological consultation are also discussed.